# What is the equation of the normal line of #f(x)=x^3+6x^2-3x# at #x=-1#?

the tangent gradient is

and the normal gradient will be calculated from

eqn of normal

By signing up, you agree to our Terms of Service and Privacy Policy

The equation of the normal line of f(x)=x^3+6x^2-3x at x=-1 is y = -10x - 1.

By signing up, you agree to our Terms of Service and Privacy Policy

- Using the limit definition, how do you differentiate #f(x) =sqrt(x−3)#?
- What is the equation of the normal line of #f(x)=((5-x)(4-x^2))/(x^3-1)# at #x=3#?
- Differentiate the function. H(x) = (x + x^−1)^3 ?
- How do you find the average rate of change for the function #f(x)=x^2# on the indicated intervals [-2,1]?
- What is the equation of the normal line of #f(x)= xsinx-cos^2x# at #x = pi/8#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7